Bothrops atrox from Ecuadorian Amazon: Initial analyses of venoms from individuals - Patiño, Ricardo (2021)
Bothrops atrox is the most clinically relevant snake species within the Amazon region, which includes Ecuadorian territories. It comprises a large distribution, which could contribute to the genetic and venomic variation identified in the species. The high variability and protein isoform diversity of its venom are of medical interest, since it can influence the clinical manifestations caused by envenomation and its treatment. However, in Ecuador there is insufficient information on the diversity of venomic phenotypes, even of relevant species such as B. atrox. Here, we characterized the biochemical and toxicological profiles of the venom of six B. atrox individuals from the Ecuadorian Amazon. Differences in catalytic activities of toxins, elution profiles in liquid chromatography, electrophoretic patterns, and toxic effects among the analyzed samples were identified. Nonetheless, in the preclinical testing of antivenom, two samples from Mera (Pastaza) required a higher dose to achieve total neutralization of lethality and hemorrhage. Taken together, these data highlight the importance of analyzing individual venoms in studies focused on the outcomes of envenoming.